The nonfarm sector and rural development: review of issues and evidence - Islam, Nurul (International Food Policy Research Institute, 1997)
This paper assembles empirical evidence on the nonfarm sector and analyzes policies for affecting future rural development. It reviews trends in trade and services, cottage industries, and small industries, among others. It examines linkages between the nonfarm and farm sectors and between the nonfarm sector and urban enterprises. It also suggests methods governments can use to promote the nonfarm sector in rural areas.